Digitalization of Mobile-Based Construction Material Inventory Management Using the Waterfall Model at PT Wanro Sukses Persada - Raihan Naufal Aulia; Nanang Hoesen Hidroes Abbrori (Universitas Negeri Surabaya, 2026)
PT Wanro Sukses Persada faces constraints in construction logistics management due to a manual material recording system, which triggers various problems such as stock data inaccuracies, delayed information updates, and discrepancies between administrative records and physical conditions in the field. Therefore, this study aims to design and develop a mobile-based material stock management and monitoring application to provide real-time data and digitize the workflow. This research employs a qualitative case study method with a Software Development Life Cycle (SDLC) Waterfall model approach without the maintenance phase, where the infrastructure is built using Android Studio integrated with Firebase Realtime Database. To validate the functionality of the developed system, this study applies Black-Box Testing, focusing on testing the alignment between the software's input and output. This research produced a mobile application named